Design and Development of A Smart Parachute Control System for Military and Civilian Applications - Akash Adhikary, Tapan Maity, Dr. Jagannath samanta (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The parachute is a folding, umbrella like fabric device which is mainly employed to slow down the fast moving objects or people in airspace. Parachutes have employed in adventure sports, military and cargo drop etc. Sometimes even after deployment these devices fail to provide safety to the diver like in case of blackout. Even the drop one of a conventional unmanned parachute cannot be manipulated much. In literature advancement in parachute technology has taken place mostly mechanically. Hence there remains a scope of development in the field of its avionics. In this paper, a model is proposed not only to deploys the parachute at a safe height but also navigates the parachute to a safe landing zone, avoiding water and trees etc. The limitations of the present model are using Global Positioning System (GPS) to guide the system. In future more robust sensors can be used and data from multiple sensors to increase the accuracy.